Key stakeholder interviews on gender inclusion and intersectionality in Colombian land, climate change and food policies - Howland, Fanny Cecile (2024)
The database contains information from interviews with government, research, social movement and international cooperation actors on the inclusion of gender and intersectionality in Colombian land, climate change and food policies